2021
DOI: 10.3390/ijms222312807
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gene Expression by Telomere Position Effect

Abstract: Many diseases that involve malignant tumors in the elderly affect the quality of human life; therefore, the relationship between aging and pathogenesis in geriatric diseases must be under-stood to develop appropriate treatments for these diseases. Recent reports have shown that epigenetic regulation caused by changes in the local chromatin structure plays an essential role in aging. This review provides an overview of the roles of telomere shortening on genomic structural changes during an age-dependent shift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 112 publications
(141 reference statements)
0
3
0
Order By: Relevance
“…The change in the expression of genes can be modulated through TPE, which was first extensively described in Saccharomyces cerevisiae [ 50 , 78 ]. Studies conducted on mammalian cells revealed that the TPE provides a mechanism to alter gene expression which depends on the distance of the gene from the telomere ends, as well as the heterochromatin looping of the telomeres themselves [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in the expression of genes can be modulated through TPE, which was first extensively described in Saccharomyces cerevisiae [ 50 , 78 ]. Studies conducted on mammalian cells revealed that the TPE provides a mechanism to alter gene expression which depends on the distance of the gene from the telomere ends, as well as the heterochromatin looping of the telomeres themselves [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…When telomeres are long, their looped structure can extend up to several megabases in length [ 78 , 80 ]. Therefore, genes that are usually farther away from the linearized chromosome ends, such as hTERT , may be silenced due to the TPE-OLD [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to protecting the ends of DNA strands, telomeres carry out additional vital tasks such as controlling the expression of genes that are either close to the telomeres (called TPE) or far from them (called TPE over long distances, or TPE-OLD). 16 The minimal length of telomeric DNA repeats and the efficiency of the related protein complexes are two factors that strictly control the function of telomeres. 17 Furthermore, it is believed that appropriate telomere function is aided by higher-order DNA conformations like the G-quadruplexes (G-rich, four-stranded nonhelical structures) and T-loop.…”
Section: Structure and Function Of Telomeresmentioning
confidence: 99%
“…For these genes to be active, they must be positioned in the telomeric region of the chromosome, even though they are located on various chromosomes. Furthermore, a multitude of separate gene families that encode outer surface proteins in Giardia have been identified and suggested to aid Giardia in evading the immune response of the host through the mechanism of antigenic diversity ( Nash, 1997 ; Faubert, 2000 ; Lee et al, 2021 ). The apicomplexan parasites of the genus Plasmodium develop in erythrocytes in repeated cycles during malaria infection.…”
Section: Protozoamentioning
confidence: 99%